Biochemical and histological changes in liver and kidney in male Wistar albino rats following exposure to Solignum®: a permethrincontaining wood preservative - Kingsley C. Patrick-Iwuanyanwu; Iniobong A. Charles (MDPI AG, 2014)
The present investigation was aimed to determine the effect of sub-chronic exposure to Solignum®, a permethrin-containing wood preservative on biochemical and histological changes in liver and kidneys of male Wistar albino rats. Thirty-two male rats were randomly divided into four groups: control and three treatment concentrations containing 8 rats each. The treatment groups were exposed to Solignum® at dose rates of 100, 200 and 400 mg/kg body weight (BW) respectively per day orally for four weeks. Data obtained from the study showed a progressive increase in the body weight of rats in control whereas, rats treated with different concentrations (100, 200 and 400 mg/kg BW) of Solignum® decreased significantly (≤0.05) especially at the end of the second and fourth week when compared with control. On the other hand, there was a significant decrease in the relative liver weights of rats treated with 100 and 200 mg/kg BW Solignum® while rats treated with 400 mg/kg BW showed a significant increase when compared with control. The relative weight of kidneys in experimental groups increased significantly when compared with control. Biochemical analysis results illustrated that there was a significant increase in marker enzymes namely alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase activity at the end of the fourth week. Similarly, total bilirubin, serum urea, creatinine and electrolytes (Na+, K+ and Cl-) levels increased in a dose dependent manner in treated rats when compared with untreated control group. Serum total protein decreased significantly in experimental rats when compared with control. However, cholesterol and triglycerides showed no significant difference when compared with control. Histopathological examination of hepatocytes in treated rats was characterized by mild periportal inflammatory cells and cytoplasmic degeneration. Furthermore, histopathological examination of rat kidneys revealed inflammatory cells, congested vessel and interstitial hemorrhage in rats treated with Solignum®. Therefore, this present study is aimed to evaluate the hepatotoxic and nephrotoxic potentials associated with sub-chronic exposure to the commercial pesticide Solignum®.